The Power of Kindness: Examining the Impact of Local Hospitality on Tourists’ Revisit Intention Across Nationalities - Insuwanno, Patthawee (Journal of Cultural Analysis and Social Change, 2026)
This study investigates the influence of perceived kindness from local residents on tourists’ emotional bonding and revisit intention, drawing on the Stimulus–Organism–Response (S–O–R) framework. As contemporary travellers increasingly seek authentic and meaningful interactions, local residents have shifted from a traditional backstage presence to a prominent front-stage role in shaping tourism experiences. Using quantitative data from 427 respondents, this study employs Structural Equation Modelling (SEM) and One-Way ANOVA to analyse the relationships among key constructs and compare regional differences. The findings reveal that perceived kindness from locals functions as a significant stimulus that enhances tourists’ emotional bonding with the destination. This emotional connection subsequently strengthens their intention to revisit, underscoring the pivotal role of human warmth in shaping post-visit behaviours. ANOVA results further indicate that among the three regional groups (Asia, Oceania, and Western), visitors from Oceania consistently reported higher perceptions of locals’ kindness, stronger emotional bonding, and higher revisit intention, followed by respondents from Asia and Western regions. This study contributes to tourism theory by empirically validating kindness as a critical socio-emotional factor within the S–O–R model and offers practical insights for destination managers aiming to foster loyalty through enhanced resident–tourist interactions.